The impact of personality traits on positivity at work and job performance of officers - An empirical investigation at the district-level administrative agencies in Hanoi - Nguyen Danh, Nam; Uong, Lan (Journal of International Economics and Management, 2023)
This study investigates the influence of personality traits on positivity at work and officer performance at the district-level administrative agencies in Hanoi. Based on the information obtained from 420 officers, the structural equation modeling was adopted to assess the impact of the Big Five model of personality on positivity at work and job performance. The results show a positive relationship between personality traits, positivity at work, and job performance. At the same time, positivity at work positively impacts officers’ job performance. These findings suggest recommendations for district-level administrative agencies to enhance positivity at work and improve officers’ performance. This paper provides empirical evidence of the feasible application of the Big Five model of personality and serves as a reference for further research on organizational behavior in both public and private organizations.